Kinetics of Starch Degradation during Extrusion Cooking of Steady State Flow Konjac (Amorphophallus oncophyllus) Tuber Flour in a Single Screw Extruder - Andri Cahyo Kumoro; Diah Susetyo Retnowati; Ratnawati Ratnawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
The presence of glucomannan in Konjac (Amorphophallus oncophyllus) tuber flour has promoted its various applications, especially in the food, drink, drug delivery and cosmetics. Starch is the main impurity of Konjac tuber flour. Although the common wet refining method may result in a high purity Konjac tuber flour, it is very tedious, time consuming and costly. This research aimed to study the kinetics of starch degradation in the extrusion cooking process of dry refining method to produce high quality Konjac tuber flour. In this research, Konjac tuber flour with 20% (w/w) moisture was extruded in a single screw extruder by varying screw speeds (50, 75, 100, 125, 150 and 175 rpm) and barrel temperatures (353, 373, 393, 413 and 433 K). The results showed that the starch extrusion cooking obeys the first reaction order. The reaction rate constant could be satisfactorily fitted by Arrhenius correlation with total activation energy of 6191 J.mol−1 and pre-exponential factor of 2.8728×10−1 s−1. Accordingly, thermal degradation was found to be the primary cause of starch degradation, which shared more than 99% of the energy used for starch degradation. Based on mass Biot number and Thiele modulus evaluations, chemical reaction was the controlling mechanism of the process. The results of this research offer potential application in Konjac tuber flour refining process to obtain high quality flour product. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).